137 Prenatal transportation stress alters genome-wide DNA methylation in suckling Brahman bull calves. (7th December 2018) - Littlejohn, B; Price, D; Neuendorff, D; Carroll, J; Vann, R; Riggs, P; Riley, D; Long, C; Welsh, T; Randel, R
Abstract: The objective of this experiment was to compare genome-wide differential DNA methylation in young prenatally stressed (PNS) and Control bull calves. Mature Brahman cows (n = 48) were transported for 2-h periods at 60 ± 5, 80 ± 5, 100 ± 5, 120 ± 5, and 140 ± 5 d of gestation or maintained as non-transported Controls (n = 48). Methylation of DNA from white blood cells from a subset of 28-d-old intact male offspring (n = 7 PNS; n = 7 Control) was assessed via reduced representation bisulfite sequencing. Compared with Control calves, PNS samples contained 16, 128, 226, and 391 differentially methylated CG, CHG, and CHH sites, respectively (C = cytosine; G = guanine; H = either adenine, thymine, or cytosine). Of the CG sites, 7, 407 were hypermethylated (significantly more methylated than Controls) and 8, 721 were hypomethylated (significantly less methylated than Controls). Increased DNA methylation in gene promoter regions typically results in decreased transcriptional activity of the region. Therefore, differentially methylated CG sites located within promoter regions (n = 1, 205) were used to predict (using Ingenuity Pathway Analysis software) alterations to canonical pathways in PNS compared with Control bull calves. In PNS bull calves, 108 pathways were altered ( P ≤ 0.05) compared to Controls. Among these were pathways related to behavior, stress response, immune function, metabolism, reproduction, and cell signaling. Predicted alterations in behavior, stress response, and reproductive endocrinology are supported by previously observed phenotypic differences in the larger population of PNS and Control calves from which bulls in this study were derived (J. Anim. Sci. 94:2:602–609; J. Anim. Sci. 95:129–138). Genome-wide differential DNA methylation and predicted alterations to pathways in Prenatally Stressed compared with Control bull calves suggest epigenetic programming of biological systems in utero .